2019
DOI: 10.5935/1415-2762.20190054
|View full text |Cite
|
Sign up to set email alerts
|

Discourses of the Community Health Agents About the Child and Adolescent With Chronic Disease Assisted in Primary Care

Abstract: Objetivo: evidenciar a discursividade de agentes comunitários de saúde acerca da contribuição de suas ações de cuidado para o manejo da doença crônica de crianças/ adolescentes na atenção primária. Método: estudo qualitativo, realizado em um município paraibano, de novembro de 2015 a maio de 2016, com 10 agentes comunitários de saúde que atuam na Estratégia Saúde da Família. Os dados foram coletados por meio da entrevista semiestruturada e interpretados com base na análise do discurso. Resultados: apurou-se qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Regarding these characterization variables, a study carried out in Kenya identified that age and educational status are likely to influence the performance of ACSs in carrying out their duties. In the findings of this study, opportunities for qualification and updating proved to be key factors for the role of ACS in child health care, and shall take place on a permanent basis, ensuring significant learning, awareness of demands, and the development of resolute actions (14) .…”
Section: Discussionmentioning
confidence: 86%
“…Regarding these characterization variables, a study carried out in Kenya identified that age and educational status are likely to influence the performance of ACSs in carrying out their duties. In the findings of this study, opportunities for qualification and updating proved to be key factors for the role of ACS in child health care, and shall take place on a permanent basis, ensuring significant learning, awareness of demands, and the development of resolute actions (14) .…”
Section: Discussionmentioning
confidence: 86%